The United Nations Counterterrorism Strategy in West Africa - OLUWASUJI, Clement Olawole; AFOLABI, Muyiwa B. (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
Terrorism has undoubtedly become a potent security issue not just to West African nations but to the entire world. September 11, 2001 experience of the United States has strategically repositioned sub-regional, regional and international organisations to employ diverse counter-terrorism measures to address the menace. This article assesses the counterterrorism strategy of the United Nations (UN) in an attempt to ascertain the relevance, adequacy and challenges of the legal, institutional and policy instruments of the UN in West Africa. It is a truism to state that the African States have been threatened with terrorism incidences. Efforts of individual states and the Economic Community of West African States (ECOWAS) are not yielding expected results due to infiltration of terrorist groups; weak government institutions; porosity of international borders, youth unemployment, poverty and a host of other internal factors. The article concludes that the UN counter-terrorism strategy has the potential, together with the existing regional and sub-regional instruments to expeditiously derogate heinous terrorist attacks and related problems in West Africa. It is recommended, therefore that, there is a need for improved collaborative efforts between UN and ECOWAS in order to achieve goals of the UN counterterrorism strategy while good governance is needed to ameliorate government weakness and failures.